Modeling the Impact of Microgravity at the Cellular Level: Implications for Human Disease - Bradbury, Peta; Wu, Hanjie; Choi, Jung Un; Rowan, Alan E.; Zhang, Hongyu; Poole, Kate; Lauko, Jan; Chou, Joshua (Frontiers in Cell and Developmental Biology, 2020)
Microgravity strongly affects morphology, proliferation, differentiation, and signal transduction in cells. For example, detailed medical studies on astronauts who returned from space missions, have shown a bone loss of 2–9% per month. Furthermore, space flights were shown to result in cardiovascular dysfunction, muscle atrophy, degradation of immune function, endocrine disorders, and space movement disorder. At present, these physiological changes are one of the major obstacles to human long-term space missions [3]. Therefore, research in microgravity is currently focused on the influence of this environmental factor on the morphology, proliferation and adhesion of isolated cells and cell cultures. Since the research in the near-Earth orbit is severely constrained by the limited number of flight opportunities, ground-based simulators of microgravity are valuable tools which provide cost-efficient platforms for gravitational research and discussed in this review. Despite acceptance for the importance of understanding the relationship between force and cell behaviour, very little is really understood about mechanotransduction and even less is known about the precise cellular biology in microgravity. This review will examine the breakthroughs in cell and disease developmental biology under microgravity condition and how this technology can provide a new paradigm into advancing our understanding of biology and diseases.